Relevance of Pre-service Elementary Teacher Education Curriculum to Real Classroom Situation - Rastogi, Anita; Goel, Chanchal (JOURNAL OF INDIAN EDUCATION, 2009)
Good education demands good teachers. But inspite of establishment of a number of teacher training institutions, it is still found that primary school instruction in general conforms to a mechanical routine. There is a growing feeling that teacher education is not effective in turning out efficient teachers. The system still prepares teachers who don’t necessarily become professionally competent and committed at the completion of initial teacher preparation programme. This highlights the need to study how far the inputs provided in the PSTE programme are relevant to classroom situation; what are the problems faced by these teachers in applying the methodologies learnt and what needs to be done for making Pre-Service Teacher Education (PSTE) programme inputs more relevant. In present study perception of teachers, working in Municipal Corporation Primary schools of NCT Delhi with the professional qualification as diploma in ETE from DIETs of Delhi has been studied regarding the relevance of ‘Teaching of Mathematics’ curriculum in Pre-service Elementary Teacher Education Programme for teaching Mathematics at primary stage. The study revealed that the content designed for ‘Teaching of Mathematics’ curriculum suits to the requirements of the elementary teachers atlarge but the way it is being transacted in teacher training institutions suffers from various lacunas.